2022
DOI: 10.1111/ans.18090
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of occult level IV nodal metastasis in tongue squamous cell carcinoma: a 20 year review

Abstract: Background The extent of neck dissection for tongue SCC is unclear owing to the potential presence of occult level IV metastasis. We aim to assess the incidence of occult level IV nodal metastasis for tongue SCC patients treated in our centre over a 20 year period. Methods A retrospective analysis of data collected from 1999 to 2019 was performed. Patients diagnosed with oral tongue SCC treated primarily with surgery and a neck dissection fulfilled the inclusion criteria. Results A total of 124 patients were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Therefore, predicting the occult cervical lymph node metastases using the depth of invasion may be helpful. Similar investigations have shown that in cases of carcinomas of the lateral border of the tongue, level II nodes are the most frequently involved site, followed by level III nodes (6,18,19).…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Therefore, predicting the occult cervical lymph node metastases using the depth of invasion may be helpful. Similar investigations have shown that in cases of carcinomas of the lateral border of the tongue, level II nodes are the most frequently involved site, followed by level III nodes (6,18,19).…”
Section: Resultsmentioning
confidence: 58%
“…OSSC most commonly develops on the sites such as lips, tongue and floor of the mouth, while some OSCCs arise in apparently normal mucosa and some may be preceded by clinically obvious premalignant lesions like leukoplakia and erythroplakia (4,5). Typically, OSCC often presents as an ulcer with prominent exophytic margins or fissures (6). It can also develop as a lump, an enlarged, hard, or fixated cervical lymph node, a white or mixed white and red lesion, an extraction socket that won't heal, or a red lesion (erythroplakia) (7,8).…”
Section: Introductionmentioning
confidence: 99%